Successful transcervical uterine flushing can be performed without or reduced dose of oestradiol benzoate in cervical relaxation protocol in Dorper ewes - Dias, Jenniffer Hauschildt; Pupin, Maria Amelia [UNESP]; Duarte, Gabriela Saloni [UNESP]; Brair, Viviane Lopes; Carvalho de Paula, Cleber Jonas; Paula de Sousa, Marco Antonio; Tavares Pereira Batista, Ribrio Ivan; Goncalves Souza-Fabjan, Joanna Maria; Franco Oliveira, Maria Emilia [UNESP]; Fonseca, Jeferson Ferreira (Wiley-Blackwell, 2020)
This study assessed the efficiency of cervical relaxation protocol using none, half or full dose (1.0 mg) of oestradiol benzoate in Dorper ewes subjected to non-surgical embryo recovery (NSER). Thirty-six pluriparous ewes received progestogen sponge (60 mg) for 9 days plus eCG administration (300 IU i.m.) 24 hr before sponge removal. Ewes were not mated and were randomly assigned to receive at 16 hr before NSER 37.5 mu g d-cloprostenol i.m. and different doses of oestradiol benzoate: 0.0 mg (0EB group; n = 12); 0.5 mg (0.5EB group; n = 12) or 1.0 mg of oestradiol (1.0EB group, n = 12). All ewes received oxytocin (50 IU) i.v. 20 min before NSER, which was performed 8 days after sponge removal. Corpora lutea were counted by transrectal ultrasonography 24 hr before NSER. After procedure, the ewes were kept in natural breeding period to check their post-NSER fertility. NSER was performed in 91.7% (33/36) of the animals with overall fluid recovery efficiency over 97% (p > .05). The cervical transposing with Hegar dilator was longer (p < .05) in 0EB (4.2 +/- 0.3 min) compared to 0.5EB (1.7 +/- 0.3 min) and 1.0EB group (1.5 +/- 0.3 min). The cervical transposing with mandrel/catheter was longer (p < .05) in 0EB (2.4 +/- 0.5 min) than 1.0EB group (1.3 +/- 0.5 min). Overall duration of uterine flushing was 25.4 min with structure recovery rate of 43.5%, with no difference among groups (p > .05). The post-NSER fertility was higher (p < .05) in 0.0EB (90%) than 0.5EB group (36.4%). In conclusion, NSER can be successfully performed in Dorper ewes by using a cervical relaxation protocol without oestradiol benzoate.
Keywords: cervical dilation; NSER; post-NSER fertility; sheep; transcervical embryo recovery